Microstructure of titanium alloy modified by high-intensity implantation of low- and high-energy aluminium ions; Surface and Coatings Technology; Vol. 391 - Ryabchikov A. I. Aleksandr Ilyich; Sivin D. O. Denis Olegovich; Bozhko I. A. Irina Aleksandrovna; Stepanov I. B. Igor Borisovich; Shevelev A. E. Aleksey Eduardovich (2020, 2020)
Title screen